Role of 1,25-Dihydroxyvitamin D(3) on Intestinal Phosphate Absorption in Rats with a Normal Vitamin D Supply - Rizzoli, R. (1977)
In vitamin D-deficient rats, impaired intestinal phosphorus (P) absorption can be corrected by 1,25-dihydroxyvitamin D(3)[1,25-(OH)(2)D(3)]. In the present study, it was investigated whether changes in 1,25-(OH)(2)D(3) production can influence intestinal P transport also in animals with a normal supply of vitamin D. The intestinal P absorption was evaluated in rats using both the in situ duodenal loop technique and the determination of the overall gastrointestinal absorption under three conditions known to influence the production of 1,25-(OH)(2)D(3): (a) variation in dietary P, (b) thyroparathyroidectomy (TPTX) with or without administration of parathyroid hormone (PTH), and (c) treatment with disodium ethane-1-hydroxy-1,1-diphosphonate (EHDP). In all circumstances changes in duodenal absorption paralleled the changes in the overall fractional absorption. (a) Lowering dietary P stimulated P absorption. (b) TPTX decreased P absorption. This effect was corrected either by the administration of PTH or by the administration of 1,25-(OH)(2)D(3). (c) EHDP, when given at a dose known to inhibit 1,25-(OH)(2)D(3) formation, decreased the duodenal P absorption in both intact and TPTX animals. This effect was corrected by 1,25-(OH)(2)D(3). In the TPTX-EHDP-treated animals, the administration of PTH did not rectify the low duodenal P absorption. These results support the thesis that, in rats with normal vitamin D supply, variations in the endogenous production of 1,25-(OH)(2)D(3) change the rate of P absorption. However, these changes are in such magnitude that they are of relatively small importance when compared to the effect of variation in the dietary intake of P. These results also strongly suggest that the action of PTH on duodenal P transport is mediated by its effect on 1,25-(OH)(2)D(3) production, inasmuch as the effect of the hormone is abolished after blocking the renal 1-hydroxylation with EHDP.